Paradise valley ebook - Carr, Robyn (Virgin River, 2010)
Welcome back to Virgin River with the books that inspired the hit Netflix series... Marine corporal Rick Sudder is home early from Iraq—his tour ended abruptly on the battlefield. The carefree boy is gone, replaced by a man who believes his future is as bleak as his mirror image. But can the passion and commitment of a young woman who has never given up on him mend his broken body and shattered heart? As the people of Virgin River rally around Rick, another recent arrival tests the tightly knit mountain town's famous welcoming spirit. Dan Brady has a questionable past, and he's looking for a place to start over. He'd like it to be Virgin River...if he can find a way in. But he never expects to find it in the arms of a woman who was as much an outcast as himself. For a favorite son returned from war and an outsider looking for a home, Virgin River offers them a chance to make peace with the men they once were...and to find the dreams they thought they'd lost. What you can expect in Paradise Valley: Small Town Romance Ex-Marine Hero New Beginnings Found Family Don't miss Robyn Carr's next uplifting novel, The Friendship Club, where four women come together at a tumultuous time in their lives, forging an unbreakable bond that will leave them all forever changed! Virgin River Novels: Book 1: Virgin River Book 2: Shelter Mountain Book 3: Whispering Rock Book 4: A Virgin River Christmas Book 5: Second Chance Pass Book 6: Temptation Ridge Book 7: Paradise Valley Book 8: Forbidden Falls Book 9: Angel's Peak Book 10: Moonlight Road Book 11: Promise Canyon Book 12: Wild Man Creek Book 13: Harvest Moon Book 14: Bring Me Home for Christmas Book 15: Hidden Summit Book 16: Redwood Bend Book 17: Sunrise Point Book 18: My Kind of Christmas Book 19: Return to Virgin River